TINJAUAN YURIDIS TERHADAP PUTUSAN KASUS PENCEMARAN NAMA BAIK DENGAN MENGGUNAKAN SOSIAL MEDIA INSTAGRAM DITINJAU DARI PASAL 310 AYAT (3) KITAB UNDANG-UNDANG HUKUM PIDANA - Danny Putera Christian; Dian Andriawan Daeng Tawang (Fakultas Hukum Universitas Tarumanagara, 2018)
The regulation of defamation is stated in the Indonesia Criminal Code, specifically it’s stated on the article 310. However, the legal rules of defamation by using social media are specifically regulated in Undang-UndangNo.19 Year 2016 About the Amendment of Undang-Undang No.11 Year 2008 About Information And Electronic Transactions. In a thesis that written by the author, the author did an analysis of the actions that have been done by a defendant who deliberately perform an action that meets the element of offense in Article 27 Paragraph (3) of Undang-Undang No.19 Year 2016 on Amendment to Law No. 11 Year 2008 About Information And Electronic Transactions. The acts committed by the defendant shall not be subject to juridical sanctions, since the criminal law also applies the reasons for the criminal offense both for justification and for reasons of forgiveness. The act committed by the defendant in Decision No.1047 / Pid.Sus / PN.JKT.SEL was analyzed as justification because the defendant committed the act to defend himself, as regulated in Article 310 Paragraph (3) of the Criminal Code . The research method whichused by the author is normative research supported by conducting interviews to cyber crime experts.